Ultra-sensitive polyaniline–iron oxide nanocomposite room temperature flexible ammonia sensor1. Issue 84 (16th September 2015) - Bandgar, D. K.; Navale, S. T.; Naushad, M.; Mane, R. S.; Stadler, F. J.; Patil, V. B.
<x xml:space="preserve">Abstract</x> We report for the first time a room temperature smart NH3 sensor based on PAni–Fe2O3 nanocomposite loading on flexible PET substrate by in situ chemical oxidative polymerization method.